Carlos Marx, civil society and socialism - Monal, Isabel (Pontifícia Universidade Católica de São Paulo, 2004)
The present text is a synthesis of talks and comments that I have delivered onthis topic recently. It was presented at the opening ceremony of the SixthLatin American Meeting of Marxist Journals, held in Montevideo inSeptember 2000. I underscore the valorization of the concept of civil societyin Karl Marx’s work. The disappearance of the State hypothesized by Marx isaccompanied by the assumption of political and administrative functions bythe popular organizations of society.